The shape of parallel surface: porous media, fluctuating interfaces and complex fluids - Mecke, Klaus (ELSEVIER SCIENCE BV, 2002)
The morphological concept of parallel surfaces in combination with curvature measures ,known from integral geometry are used to characterise and model complex spatial structures beyond the two-point correlation function and to predict for instance, percolation thresholds in porous media. Applied to liquid interfaces one :finds :a;reduction of the surface tension at microscopic scales in good agreement with X-ray scattering experiments. (C) 2002 Elsevier Science B.V. All fights reserved.